PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN DIUKUR DENGAN NILAI EVA MOMENTUM (STUDI PADA PERBANKAN YANG MENDAPAT PERINGKAT CORPORATE GOVERNANCE PERCEPTION INDEX (CGPI) DAN LISTING DI BEI PERIODE 2008-2014) - UYUN, QURROTUL (Jurnal Akuntansi AKUNESA, 2016)
This study aims to determine the effect of the application of Good Corporate Governance (GCG) to the financial performance of banks. GCG variables in the study using the indicator scores GCG implementation, while financial performance variables using EVA Momentum indicator values. This study uses a quantitative approach. The population of this study is listed on the Stock Exchange banking. The selection sample of the study using purposive sampling techniques with banking criteria which follow IICG survey and got a rating score of Corporate Governance Perception Index (CGPI) 2008-2014. Hypothesis testing is done by statistical method through simple regression analysis. The results of this study indicate that GCG has no effect on the financial performance.